Revised recommendations from the CSO-HNS taskforce on performance of tracheotomy during the COVID-19 pandemic – what a difference a year makes - D. D. Sommer; D. Cote; T. McHugh; M. Corsten; M. A. Tewfik; S. Khalili; K. Fung; M. Gupta; N. Sne; P. T. Engels; E. Weitzel; T. F. E. Brown; et al. (Journal of Otolaryngology - Head and Neck Surgery, 2021)
Abstract Background During the early part of the COVID-19 pandemic, the Canadian Society of Otolaryngology - Head & Neck Surgery (CSO-HNS) task force published recommendations on performance of tracheotomy. Since then, our understanding of the virus has evolved with ongoing intensive research efforts. New literature has helped us better understand various aspects including patient outcomes and health care worker (HCW) risks associated with tracheotomy during the COVID-19 pandemic. Accordingly, the task force has re-evaluated and revised some of the previous recommendations. Main body Based on recent evidence, a negative reverse transcription polymerase chain reaction (RT-PCR) COVID-19 swab status is no longer the main deciding factor in the timing of tracheotomy. Instead, tracheotomy may be considered as soon as COVID-19 swab positive patients are greater than 20 days beyond initial symptoms and 2 weeks of mechanical ventilation. Furthermore, both open and percutaneous surgical techniques may be considered with both techniques showing similar safety and outcome profiles. Additional recommendations with discussion of current evidence are presented. Conclusion These revised recommendations apply new evidence in optimizing patient and health care system outcomes as well as minimizing risks of COVID-19 transmission during aerosol-generating tracheotomy procedures. As previously noted, additional evidence may lead to further evolution of these and other similar recommendations. Graphical abstract